2014
DOI: 10.1155/2014/292087
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Design for Two-Way AF Relay Networks

Abstract: Conventional designs on two-way relay networks mainly focus on the spectral efficiency (SE) rather than energy efficiency (EE). In this paper, we consider a system where two source nodes communicate with each other via an amplify-and-forward (AF) relay node and study the power allocation schemes to maximize EE while ensuring a certain data rate. We propose an optimal energy-efficient power allocation algorithm based on iterative search technique. In addition, a closed-form suboptimal solution is derived with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We assume that g s 1 s 2 = |h s 1 s 2 | 2 σ 2 , which reflects the instantaneous channel gain to noise ratio (CNR) [18] from the node S 1 to node S 2 . Then, the transmission rates at the two source nodes can be expressed as…”
Section: Dt Modementioning
confidence: 99%
See 1 more Smart Citation
“…We assume that g s 1 s 2 = |h s 1 s 2 | 2 σ 2 , which reflects the instantaneous channel gain to noise ratio (CNR) [18] from the node S 1 to node S 2 . Then, the transmission rates at the two source nodes can be expressed as…”
Section: Dt Modementioning
confidence: 99%
“…In [17], it has been demonstrated that the circuit power is consumed by signal processing and the device working in the active mode. The authors in [18] designed an optimal power allocation scheme to maximize EE for two-way amplify and forward (AF) relay networks with consideration of circuit power. Furthermore, the discussions above mainly focus on a fixed transmission mode, in which EE is not always the maximum at a range of transmission rate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, problem (8) is a DC problem which is known to be non-convex and NP-hard to solve [21]. Nevertheless, by replacing the concave elements with minus signs by scalar variables, the objective function is turned into a concave function and an equivalent reformulation is given by (9) Compared to (8), the non-convexity in (9) is localized in the inequality constraints , . To deal with the non-convex constraints, we propose to linearize the logarithmic function using its first order Taylor expansion, i.e., the first order Taylor polynomial approximation of at is defined as .…”
Section: B Energy Efficient Relay Amplification Matrixmentioning
confidence: 99%
“…When two-way relaying (TWR) networks are considered, major contributions to EE optimization deal with power allocation [6]- [10]. More specifically, researches in [6]- [9] study an AF TWR network with only single antenna nodes. Only the work in [10] considers a TWR network with multiple single antenna relays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation